(untitled) (Світ фінансів, 2017)
Надал С. В., Спасів Н. Я. Теоретична концептуалізація формування та сучасний прагматизм фінансування об’єднаних територіальних громад. Проведено дослідження теоретичних засад формування об’єднаних територіальних громад, виокремлено особливості їх об’єднання, висвітлено умови та прерогативи цього процесу в умовах запровадження бюджетної децентралізації. Проведено аналіз фінансування об’єднаних територіальних громад (ОТГ) за умов створення сприятливого клімату щодо їх об’єднання, висвітлено основні напрямки покращення фінансування ОТГ в умовах перманентних кризових явищ сформовано низку пропозицій щодо опти-мізації виконання показників доходів бюджетів ОТГ. Надал С. В., Спасив Н. Я. Теоретическая концептуализация формирования и современный прагматизм финансирования объединенных территориальных общин. Проведено исследование теоретических основ формирования объединенных территориальных общин, выделены особенности их объединения, освещены условия и прерогативы данного процесса в условиях внедрения бюджетной децентрализации. Проведен анализ финансирования объединенных территориальных общин (ОТО) при условии создания благоприятного климата по их объединению, обосновано основные направления улучшения финансирования ОТО в условиях перманентных кризисных явлений, сформирован ряд предложений по оптимизации выполнения показателей доходов бюджетов ОТО. Nadal S., Spasiv N. Theoretical conceptualization of formation and modern pragmatism of financing of united territorial communities. Introduction. The association of territorial communities is an effective means of providing financial resources for less developed and financially untenable territorial communities on the basis of equal access to all social services and economic benefits that are the vision of the European future. In modern conditions the implementation of this process is a multi-stage and troublesome work based on the will of representatives of territorial communities, tax capacity and economic development of territories ready for unification, parity in the context of providing social services to all members of the association, as well as distribution and redistribution of financial resources on the basis of a full partnership with the participation of communities in the implementation of powers. Purpose. The purpose of the article is to study the theoretical foundations of the formation of united territorial communities, assessment of the formation and implementation of budget revenues of the combined territorial communities on the background of permanent crisis phenomena which significantly affect the indicators of economic and social development of administrative-territorial units and the state as a whole. Result. Defining the essence of territorial communities, debating about the nature, causes of its occurrence, the consequences of its creation the undeniable advantages concerning the formation of territorial communities were established, which are the association of territorial, human, intellectual and financial potentials; the joint communal property and disposal of municipal property; permanent interaction in the process of realization of common interests. The essence of the territorial community as an independent administrative-territorial unit was determined, in which residents united by permanent residence within the village, settlement, city through the voluntary combination of intellectual and financial resources carry out their vital functions in order to ensure their own well-being and the development of a certain territory. Taking into account national realities, the dominant features of the united territorial communities were established, in particular: the voluntary basis of association on the principles of parity; the availability of a single administrative center; the unity of local interests and their separation from state interests and interests of separate territorial units; the separation of material and financial base; the possibility of adopting of local normative legal acts within the Constitution and the laws of Ukraine; positioning by the primary subject of local self-government. Summing up the results of the estimation of the income base of the united territorial community budgets of the Ternopil region it has been established that the association undoubtedly benefited these territories and communities as their own resources have increased significantly as a result of the increase of the tax base, ensuring the payment of taxes by enterprises directly at the place of the activity and placement of production facilities and not at the place of registration, as well as the ability to manage their own financial resources exclusively by the councils of united territorial communities with the transition of the communities themselves to direct inter-budgetary relations with the state. Conclusion. It has been determined that united territorial communities on the path of voluntary association and full financial independence on purpose of further existence and support of the livelihoods of members of territorial communities that have united, in addition to significant financial potential should receive at the legislative level the consolidation of the changes listed in the article and the specification of the provisions of the current normative-legal ensuring in the context of the association, which subject to the consolidation of the efforts of the central and local authorities will create further grounds for the formation of capable, self-sufficient, financially independent and economically powerful united territorial communities aimed at improving the welfare of their inhabitants.